American Made: Hollywood and the “Technicolored Magnificence of the Great American Dream” in Filipino and Filipino American Fiction - Patrick Joseph Caoile (Comparative Literature: East & West, 2025)
In Filipino and Filipino American fiction, the American Dream is a prevalent theme. Specifically, Filipinos’ exposure to the American Dream is facilitated through forms of American media and entertainment. These mediated American spectacles present the myth that the United States is superior in all aspects. This is evident in Nick Joaquin’s The Woman Who Had Two Navels, Jessica Hagedorn’s Dogeaters, Lysley Tenorio’s “Monstress,” and Bino A. Realuyo’s The Umbrella Country, in which Filipino characters internalize U.S. supremacist beliefs and what E.J.R. David calls “colonial mentality” by adopting Western American standards in their everyday lives. Their desire to emulate the American Dream is further seen in their inevitable migration from the Philippines to the U.S. These works of fiction demonstrate the relationship between media and culture, especially as theorized by Marxist critics such as Guy Debord and Stuart Hall who view media as one of the primary tools of dominant societies to disseminate and uphold hegemonic ideologies. By exploring how American media affects Filipinos in these works of fiction, one can see how media plays a significant role in some Filipinos’ beliefs about the Philippines and the U.S. especially in this contemporary age of globalization and mass media.